Kepemimpinan Perempuan dalam Gereja: Membongkar Mitos dan Meninjau Realitas - Mahardika, Amadea Prajna Putra; Tanjung, Leo Perkasa (Media: Jurnal Filsafat dan Teologi, 2024)
This paper aims to investigate history, analyze concrete cases, and provide an in-depth look at whether and how women can play leadership roles in the Church. The method used in this research is a literature study. The case study method was also used with Sr Ann Rose Nu Tawng from Myanmar as the subject. The important result of this research is that women's leadership in the Church has a very vital function. In fact, women's leadership has various characteristics and advantages that cannot be replaced by men. Church history has proven that. Finally, the conclusion of this paper is that women should be given more opportunities and trust to take on leadership roles in the Church for the good of the Church itself.